A simple model for predicting walking energetics with elastically-suspended backpack. Issue 16 (8th December 2016) - Li, Dejun; Li, Tong; Li, Qingguo; Liu, Tao; Yi, Jingang
Abstract: An elastically-suspended backpack offers biomechanical benefits by reducing peak interaction force, joint loads and chances of potential injuries as shown in previous studies. But whether it will reduce metabolic cost of the carrier (compared with the stiffly-attached pack) depends on the relation between the natural frequency of the suspension and walking frequency. Yet, no quantitative method can precisely evaluate to what extent the elasticity of suspension affects human walking energetics. We employ a single degree of freedom (DOF) model to quantitatively evaluate the effect of stiffness and damping of pack on human energetics. A surrogate of metabolic cost is proposed and utilized to estimate the energetics difference between carrying backpacks of different stiffness. The predicted difference is consistent with former backpack studies. The analysis reveals that the energy cost increases around the resonant frequency and the difference gets more significant at higher walking speeds or with heavier loads. This method gives closer energetic estimation compared with previous studies. Yet there is potentially an underestimation of the energy difference indicating later models should contain horizontal motion to obtain more precise prediction.